Disclosing compliant and responsible corporations: CSR performance in Malaysian CEO statements - Kumaran Rajandran; Fauziah Taib (Penerbit Universiti Kebangsaan Malaysia, 2014)
In Malaysia, corporate social responsibility (CSR) is relatively new but corporations are required to engage in and disclose CSR. CSR reports are a common register for disclosure and their CEO Statements provide an overview of CSR performance in these reports. This article studies how language features in Malaysian CEO Statements disclose CSR performance. A corpus containing 27 CEO Statements from 2009 to 2011 from 10 Malaysian corporations was analyzed. The analysis was grounded in critical discourse analysis (CDA), which employed Social Actors and ATTITUDE from Systemic Functional Linguistics (SFL) and interviews with corporate representatives to understand the ideology of CEO Statements. The analysis proposes three strategies of categorization, evaluation and chronology to disclose CSR performance because performance is oriented to four categories (community, environment, marketplace, workplace) and a positive evaluation, which are centered on the past. The disclosure reflects the ideology of CEO Statements, which promotes corporations as agents of positive social change. Through CEO Statements, corporations disclose compliance to the government and stock exchange and responsibility to their other stakeholders. CSR disclosure in CEO Statements helps to strengthen economic legitimacy through social legitimacy. This study is useful for people practicing and teaching corporate communication because it encourages them to consider the meaning implied by language features (evaluative and non-evaluative lexis, modifiers, tenses and prepositional phrases, besides exact numbers) in corporate registers. Yet, the corpus was limited to 27 CEO Statements and future research should expand the corpus to represent CEO Statements from other years, countries and languages.